Do Attachment Style and Emotion Regulation Strategies Indicate Distress in Predictive Testing?. Issue 5 (3rd February 2015) - van der Meer, Lucienne B.; van Duijn, Erik; Giltay, Erik J.; Tibben, Aad
Abstract: Predictive genetic testing for a neurogenetic disorder evokes strong emotions, and may lead to distress. The aim of this study is to investigate whether attachment style and emotion regulation strategies are associated with distress in persons who present for predictive testing for a neurogenetic disorder, and whether these psychological traits predict distress after receiving test results. Self‐report scales were used to assess attachment insecurity (anxiety and avoidance) and maladaptive emotion regulation strategies (self‐blame, rumination, catastrophizing) in adults at 50 % risk for Huntington's Disease (HD), Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL), and Hereditary Cerebral Hemorrhage With Amyloidosis ‐ Dutch type (HCHWA‐D), when they presented for predictive testing. Distress was measured before testing and twice (within 2 months and between 6 and 8 months) after receiving test results. Pearson correlations and linear regression were used to analyze whether attachment style and emotion regulation strategies indicated distress. In 98 persons at risk for HD, CADASIL, or HCHWA‐D, attachment anxiety and catastrophizing were associated with distress before predictive testing. Attachment anxiety predicted distress up to 2 months after testing. Clinicians may consider looking for signs of attachment anxiety and catastrophizing in persons who present for predictive testing, to see who may be vulnerable for distress during and after testing.